Butterfly Jump - Lewis, Mary Catherine (2019)
Butterfly Jump tells the story of a scrappy, overweight woman from the wrong side of the tracks who is a single parent determined to have her children fit into the upper crust. Connie Noseworthy sends her children to a private Catholic school that educates in the Jesuit tradition of social justice thanks to a tuition assistance program for people in financial need. When Connie is judged by that world and her children are wrongfully removed from her care due to assumptions rooted more in class prejudices than fact, she must fight the system to get them back. In doing so, she undergoes a radical personal transformation. This film looks at working class life and its intersection or clash with the upper crust while telling a story of inner growth and spiritual transformation. Connie Noseworthy is our protagonist whose story carries the heart of the film.